Antioxidant Activities of Root, Stem and Leaves of Vernonia ci nerea (L) Less. - Goggi, Arti; Malpathak, Nutan (Free Radicals and Antioxidants)
Background: Vernonia cinerea (L) Less has ethnomedicinal importance and is well known for its anti-inflammatory and anticancerous properties. Objective: Present study investigates antioxidant activity of various crude extracts prepared from different organs of plant such as Root, Stem and Leaves using polar and nonpolar solvents. Materials and methods: The antioxidant activity was determined using different methods which includes radical scavenging assays (DPPH and ABTS) and phosphomolybdenum assay. LC- MS profiling was performed for the extracts showing maximum antioxidant activity to identify bioactive constituents. Result: Difference was observed in the antioxidant activities of extracts by different methods. Significant (p< 0.05) antioxidant activity was exhibited by different organs of a plant and different extracts. LC-MS analysis revealed the presence of phenols, terpenoids, quinones and steroids in the extracts. Conclusion: Different antioxidant assays help in knowing the antioxidant potential of different crude extracts. The bioactive constituents identified can be correlated to antioxidant activity and used in drug formulations.
Keywords: ABTS; DPPH; LC-MS; Phosphomolybdenum; Vernonia cinerea